Comparison of switch to the highest dose of rosuvastatin vs. add‐on nicotinic acid vs. add‐on fenofibrate for mixed dyslipidaemia. Issue 5 (20th March 2013) - Kei, A.; Liberopoulos, E. N.; Mikhailidis, D. P.; Elisaf, M.
Summary: Background: Use of a statin at a standard dose may be insufficient for the treatment of mixed dyslipidaemia. Whether switch to the highest dose of rosuvastatin (40 mg) or add‐on nicotinic acid (NA) or fenofibrate is more efficacious remains unknown. Patients and methods: This was a prospective, randomised, open‐label, blinded end‐point (PROBE) study. We recruited 100 patients with mixed dyslipidaemia who were treated with a statin at a standard dose but had not achieved lipid targets. Patients were randomised to switch to the highest approved dose of rosuvastatin (40 mg), add‐on extended release nicotinic acid (ER‐NA)/l‐aropiprant (LRPT) or to add‐on micronised fenofibrate for 3 months. The primary end‐point was the change in non‐high‐density lipoprotein cholesterol (non‐HDL‐C) levels. Results: Ninety patients completed the study. Non‐HDL‐C decreased in all groups (by 23, 24 and 7% in the rosuvastatin, ER‐NA/LRPT and fenofibrate group, respectively, p < 0.01 for all compared with baseline and p < 0.01 for all compared with fenofibrate group). Low‐density lipoprotein cholesterol (LDL‐C) decreased by 23 and 19% in the rosuvastatin and ER‐NA/LRPT group, respectively (p < 0.01 compared with baseline), but not in the add‐on fenofibrate group. Add‐on ER‐NA/LRPT was associated with the greatest HDL‐C increase, while add‐on ER‐NA/LRPT and add‐on fenofibrate were associated with the greatest triglyceride decrease. Twenty‐four per cent of patients initially randomised to add‐on ER‐NA/LRPT dropped out because of side effects. Conclusions: In conclusion, switch to the highest dose of rosuvastatin and add‐on ER‐NA/LRPT may be better options compared with add‐on fenofibrate for the management of patients with mixed dyslipidaemia not on treatment goals with a statin at a standard dose. Abstract : Linked Comment: Wierzbicki. Int J Clin Pract 2013; 67: 391–3. Linked Comment: www.youtube.com/IJCPeditorial